The implications of the pandemic for the corporate governance, remuneration and sustainability performance of South African listed companies - Ajeigbe, Kola Benson; Ganda, Fortune (International Journal of Innovative Research and Scientific Studies, 2023)
The study examined the implications of the recent pandemic on the corporate governance, remuneration and corporate sustainability performance of South African listed companies. Data from 42 companies was analyzed using the panel fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) methods from 2010-2021. Findings revealed that the pandemic negatively impacted the selected companies. This study revealed that the pandemic had a good impact on some companies and not just bad ones as claimed by previous researchers. Results from COVID -19- related expenses, debt-to-equity ratios and staff costs revealed a negative but significant result in the estimated model. Other variables such as current ratios, net profit margins and board diversity revealed a positive and significant relationship with all the dependent variables. Hence, a very severe implication of the pandemic on the performance of companies is confirmed through COVID -19related expenses, staff costs and directors’ remuneration. These have a very strong negative impact on the future performance, survival, and sustainability of the selected companies. Lastly, a strong relationship between corporate governance and corporate sustainability performance was confirmed as shown by ROA, board size, directors’ remunerations and board diversity. This study provides insight for stakeholders such as governments, directors and policymakers to develop both preventive and proactive policies to protect and guide companies from future similar pandemics. To avert and prevent future negative implications on companies, this study recommends a well- structured scheme for all of the company’s staff, cash reserves and IT governance.